Mechanism for pollination in African yam bean (2016)
African yam bean (AYB) (Sphenostylis stenocarpa (Hochst Ex. A. Rich) Harms is a neglected and underutilised legume in tropical Africa. Its utilisation has been hampered by the presence of anti-nutritional factors and lack of improved varieties. The objective of this study was to investigate pollination and determine the rates of selfing and outcrossing in the species. Accession TSs5 had the highest fruit set (63.16%) in the open-pollinated breeding method; while AYB50 had the lowest value (46.61%). Seed set in the selfed accessions ranged from 91.45% (AYB50) to 94.97% (TSs66). Fruit set was highest in the open-pollinated breeding method, with a mean average fruit set of 51.32%. Significant differences (P < 0.01) were obtained in fruit set from accessions isolated with net bags which had the lowest seed set (88.91%) Seed set was highest (92.92%) in the selfed accessions. The self incompatibility index ranged from 1.33 to 2.26 and the rate of fruit set from artificial self-pollination was greater than 30% in the field, and the screen house showing that the species is highly self compatible. Selfing and outcrossing rates of 91.38 and 8.62% showed that S. stenocarpa is not an obligate selfer. AYB sets fruits and seeds when open pollinated, isolated, selfed or crossed with other accessions.